How poor is Turkey? And what can be done about it? - Ajit Zacharias; Thomas Masterson; Emel Memiş (Levy Economics Institute of Bard College, 2014)
Gauging the severity of poverty in a given country requires a reasonably comprehensive measurement of whether individuals and households are surpassing some basic threshold of material well-being. This would seem to be an obvious point, and yet, in most cases, our official poverty metrics fail that test, often due to a crucial omission. In this policy brief, Senior Scholar Ajit Zacharias, Research Scholar Thomas Masterson, and Research Associate Emel Memiş present an alternative measure of poverty for Turkey and lay out the policy lessons that follow. Their research reveals that the number of people living in poverty and the severity of their deprivation have been significantly underestimated. This report is part of an ongoing Levy Institute project on time poverty (the Levy Institute Measure of Time and Income Poverty), which has produced research on Latin America, Korea, and now Turkey, with the aim of extending this approach to other countries.
Keywords: 330